Children's news in Australia: content for young readers in Crinkling News. Issue 1 (2nd January 2019) - English, Peter; Barnes, Renee; Fynes-Clinton, Jane; Stewart, Leicha
ABSTRACT: Children have traditionally been neglected in the study of news. The emergence of Crinkling News, the only national newspaper specifically produced for young Australians, drew widespread attention before it closed after 20 months of publication in 2018. With the Australian media in a state of flux, the initial success of this newspaper highlighted the importance of introducing children to media literacy. This paper explores the characteristics of the presentation of news for children through the pages of Crinkling News . Utilising news values, this study also investigates the selection of angles and how stories and information are packaged for young audiences. It will examine how traditional content is mixed with user-generated contributions. Drawing on a content analysis of 12 months of issues, the paper outlines the type of coverage and story topics used to engage children in journalism. By providing key insights into generational access to news, this paper develops further understanding into children's media literacy and provides recommendations for future scholarship. It also highlights the importance of enabling children's participation in news as part of the critical public sphere.